2017
DOI: 10.1038/cddis.2017.400
|View full text |Cite
|
Sign up to set email alerts
|

RNF183 promotes proliferation and metastasis of colorectal cancer cells via activation of NF-κB-IL-8 axis

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors worldwide, which is a heterogeneous disease and main risk factors are associated with inflammation, family history, genetic mutations, epigenetics, and so on. Ring finger domain proteins have been reported involved in carcinogenesis, whereas their roles in CRC are rarely studied. Here, we reanalyzed the expression of 202 RNF family members in CRC using published microarray data from GEO database and found that RNF183 is markedly upregulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 35 publications
3
43
0
1
Order By: Relevance
“…Transcriptome analysis revealed that Sema7A expression was significantly higher in EGFR-Mut-expressing cells than in cells expressing the WT receptor ( Figure 1B and Table 1; all gene expression data have been submitted to GEO, accession number GSE104494). Also upregulated were Lgr6 and Rnf183, which have been implicated in lung cancer stem-like cells and progression of colon cancer, respectively (30,31). Therefore, we focused on SEMA7A.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptome analysis revealed that Sema7A expression was significantly higher in EGFR-Mut-expressing cells than in cells expressing the WT receptor ( Figure 1B and Table 1; all gene expression data have been submitted to GEO, accession number GSE104494). Also upregulated were Lgr6 and Rnf183, which have been implicated in lung cancer stem-like cells and progression of colon cancer, respectively (30,31). Therefore, we focused on SEMA7A.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study suggested that TSLNC8 was downregulated in human glioma, which was associated with increased cell proliferative rate and cell metastasis, as well as the decreased cell apoptotic capacity in human glioma cell lines; TSLNC8 may be a potential therapeutic target for cancer patients in clinic. Cell proliferation and cell metastasis are two primary manifestations in the majority of malignancies (24,25). Initiation of metastasis requires invasion, which was examined in the present study via Transwell and wound-healing assays.…”
Section: Discussionmentioning
confidence: 99%
“…RNF183 has been described as a ubiquitin ligase, which is expressed in normal colonic epithelial cells and colorectal cancer cells (19,20). In addition, we previously reported that Rnf183 mRNA expression in the kidney is ϳ324-fold higher than in the colon (21); however, RNF183 protein expression in the kidney remains unclear.…”
Section: Rnf183 Is Predominantly Expressed In the Renal Medullamentioning
confidence: 98%
“…(ii) In the colon, RNF183 degrades IB␣, thereby inducing NF-B activation, which might contribute the pathogenesis of IBD (19). (iii) In the colorectal cancers, RNF183 induces the activation of NF-B and expression of its downstream gene, IL8, resulting in increased proliferation and metastasis of colorectal cancer cells (20). However, FATE1 expression is restricted to cancer or testis and is absent in the other tissues, such as the kidney (45).…”
Section: Nfat5 Regulates Rnf183 Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation